(untitled) (Innovaciones Educativas, 2022)
Plagiarism has been the subject of research for some years; nonetheless, it has been studied primarily in students of different educational levels, although it is a practice that is also manifested in scientific research. Therefore, this article starts by answering the question: What is the prevalence of plagiarism among researchers? What are the leading causes associated with it? What strategies are used to prevent it? We performed a systematic literature review. A total of 25 documents were evaluated, analyzed, and synthesized. The results indicate that the prevalence of plagiarism is 4.3% at the international level, a percentage below the actual practice due to response bias: some researchers may not report the commission of plagiarism in their research practice, even when their participation is anonymous. The main reason for plagiarism is lack of time, which is related to excessive work and pressure to achieve a promotion. Prevention strategies are grouped into three: implementation of training, creation or modification of policies and documents. Despite initially focusing on plagiarism, this review adds information on other unethical research practices. In conclusion, despite its apparent low prevalence, plagiarism is an alarming phenomenon in scientific research. It requires a clear and complete definition to be accepted internationally, and it needs to be studied further and with different methodologies. This work offers suggestions for new lines of research as well as prevention strategies.